Effect of fungicides and bio-agents on powdery mildew of coriander (Coriandrum sativum L.) - Banwasi Rakesh, Singh Kumar Ajit (Journal of Spices and Aromatic Crops, 2012)
Various fungicides and biocontrol agents were evaluated for the management of powdery mildew of coriander (Coriandrum sativum L.) at Raigarh (Chhattisgarh). The results showed that minimum disease intensity (20.6%) and maximum yield (810 kg ha-1) were obtained with application of carbendazim as soil drench and 0.1% spray at 60 days after sowing which was on par with spray of wettable sulphur 0.2% at 60 days after sowing (T6). Cost:Benefit ratio (2.08) was highest with wettable sulphur 0.2% spray at 60 days after sowing.